Quanton Based Model of Field Interactions, (JOURNAL OF ADVANCES IN PHYSICS, 2022)
The search for a unification of the physical phenomena was the preoccupation of many physicists for long time. Starting from the seventeenth century with the unification of celestial mechanics and gravitation, then the unification of the electromagnetism in the nineteenth century. The early twentieth century brought about the unification of space and time and the unification of energy and mass while the advent of gauge theory enabled the unification of the weak interaction with the electromagnetism in the middle of the twentieth century. More recent theories are proposed as the answer to the unification question in physics include quantum gravity which unifies quantum mechanics and gravitation, and string theory. Unification effort should not only address the known fundamental forces but the space fabric interactions which till now remain unknown but their manifestations are described as the dark energy and dark matter. Here the concept of interacting space and time fields which constitute space time is discussed using classic method which has a certain advantage of bringing the physical meaning into visualization.